Stability study of veterinary drugs in standard solutions for LC-MS/MS screening in food. Issue 4 (3rd April 2018) - Desmarchelier, Aurélien; Feuerrigel, Philipp; Fathi Ahmed, Hassan; Moulin, Julie; Beck, Andrea; Mujahid, Claudia; Bessaire, Thomas; Savoy, Marie-Claude; Mottier, Pascal
ABSTRACT: A study on stability of veterinary drugs in standard solutions stored at −80°C and at −20°C was conducted over 1 year. Data were acquired on 152 individual stock standard solutions and also on 15 family mixes and 2 working standard solutions. All solutions were prepared, stored and compared 1 year later against freshly prepared ones by LC-MS/MS. A statistical analysis was performed to set the acceptability criteria, taking into account the variability of standard preparations. In individual stock standard solutions stored at −80°C (12 months) and −20°C (9 months), stability was demonstrated for 141 and 140 out of 152 compounds, i.e. for 92% and 93% of compounds, respectively. Drugs were even more stable when solubilised in either diluted family mixes or working standard solutions, with more than 99% and 94% of compounds found unaltered when stored at −80°C and at −20°C, respectively. In mixes, beta-lactams from the cephalosporin (cefadroxil and cephalexin) and penicillin (amoxicillin and ampicillin) families were found to be the least stable compounds when stored at −20°C (6 months), necessitating storage at −80°C to achieve a 1-year shelf life. The study also evidenced solubility issues for two sulfonamides (sulfadiazine and sulfamerazine) in methanol-based solutions. An independent stability study conducted by a second laboratory confirmed the 1-year stability of 3 family mixes—quinolones, sulfonamides and tetracyclines.